Phage combination alleviates bacterial leaf blight of rice (Oryza sativa L.) - Jiang, Hubiao; Li, Changxin; Huang, Xuefang; Ahmed, Temoor; Ogunyemi, Solabomi Olaitan; Yu, Shanhong; Wang, Xiao; Ali, Hayssam M.; Khan, Fahad; Yan, Chengqi; Chen, Jianping; Li, Bin (Frontiers in Plant Science, 2023)
Rice bacterial leaf blight (BLB) is the most destructive bacterial diseases caused by Xanthomonas oryzae pv. oryzae (Xoo). Phages have been proposed as a green and efficient strategy to kill bacterial pathogens in crops, however, the mechanism of action of phages in the control of phyllosphere bacterial diseases remain unclear. From the glasshouse pot experiment, the control effect of phages against BLB was evaluated and the disease index was found to be reduced to 64.3 %. High-throughput sequencing technology was used to analyze the characteristics of phyllosphere microbiome changes and the results showed that adding phage combinations increased the diversity of the bacterial community and partially recovered it. The abundance of sensitive modules in phyllosphere bacterial communities was highly associated with the disease index. Additionally, the phage combination improved the abundance of potentially beneficial bacteria such as Sphingomonas and Stenotrophomonas while reducing the relative abundance (RA) of Xoo. According to structural equation modeling, phage combinations had both direct and indirect effects on the disease index by affecting pathogen Xoo biomass and phage resistance. In summary, phages can reduce disease occurrence by reducing the biomass of pathogen Xoo and increasing the resistance of pathogen Xoo to phages. These findings does not only provide new insights into phage biological control of phyllosphere bacterial diseases but also provide theoretical data support and new ideas for agricultural green prevention and control of phyllosphere diseases.